PENGARUH PEMBELAJARAN ONLINE(E-LEARNING) TERHADAP MOTIVASI BELAJAR MAHASISWA PROGRAM STUDI BIMBINGAN DAN KONSELING UNIVERSITAS PALANGKA RAYA ANGKATAN 2018 - Ni Wayan Widya Fitriani; Romiaty; Oktamia Karuniaty Sangalang (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2021)
ABSTRACT This study to determine the contribution of online learning (e-learning) of students in the Guidance and Counseling Study Program of the University of Palangka Raya 2018. It is hoped that the application of online learning during the corona virus or covid 19 pandemic will not change the effectiveness and quality of student learning, where this is also determined by learning motivation. The subjects of this study were 44 student. The research used is ex-post facto research that is correlational with a non-experimental quantitative approach. From the results of the study using the product moment correlation analysis obtained r count = 0.640 seeing the 5% significance level in the r product moment table with a sample size of 44 people and dk = n - 2 is 0.304. thus the value of r count> r table, and a significance value (Sig. (2-tailed)) of 0.000 <0.05 is obtained, so Ho is rejected and Ha is accepted. It can be interpreted that the degree of correlation or influence between online learning (e-learning) variables (X) and learning motivation (Y) is strong, lies in the coefficient interval 0.60 - 0.799 where the lower online learning (e-learning), the lower the motivation learn. Can be concluded that online learning (e-learning) has an effect on the learning motivation of student in the Guidance and Counseling Study Program of the University of Palangka Raya 2018.